Índice de Actas del I Coloquio sobre Lenguas y Culturas Prerromanas de la Península Ibérica (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This work offers the complete index of Actas del I Coloquio sobre lenguas y culturas prerromanas de la Península Ibérica, an instrument that improves the workability and accessibility of contributions made of the Symposium of which had been published only those of J. Corominas.
Keywords: Paleohispanic languages; Paleohispanic Terms; Onomastics; Acta Palaeohispanica I; Index